PENINGKATAN KINERJA APARATUR PEMERINTAH DESA BERBASIS APLIKASI PAHARI DI KABUPATEN PULANG PISAU: IMPROVING THE PERFORMANCE OF VILLAGE GOVERNMENT APPARATUS BASED ON THE PAHARI APPLICATION IN PULANG PISAU DISTRICT - Pasaribu, Muhammad Irvan Yazid Azhar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
This research aims to see the picture of public services before and after the existence of application-based services. The presence of the PAHARI Application is intended so that the performance of Village Government Apparatus can provide integrated, integrated, standardized and comprehensive administrative services in realizing excellent service. The method in this research is descriptive qualitative with research subjects namely the PMDes Service as the initiator of the application, the Government Section of the Regional Secretariat as the developer of the application and the Village Government Apparatus as the research object as the provider of services to the community in Pulang Pisau Regency, Central Kalimantan. Data collection uses interview, observation and documentation techniques. The results of this research are that the PAHARI Application can improve the performance of Village Government Apparatus in providing maximum administrative services and can be resolved by developing the PAHARI Application which is innovative, advanced, just and prosperous.